Elastostatic loading rejuvenation behavior in bulk metallic glasses and its origin: A review - Seyyedeh Maryam Mirhashemi; Mehdi Malekan (Journal of Materials Research and Technology)
Bulk metallic glasses (BMGs) that exhibit superior properties compared to their crystalline counterparts, such as high strength, excellent corrosion resistance and good magnetic properties, are emerging as advanced engineering materials. However, due to the localization of deformation in one or several shear bands, most have low plasticity at ambient temperature. Rejuvenation is an effective technique to overcome this limitation without changing the composition. In the present review article, the concept of rejuvenation and the effects of rejuvenation on the properties of BMGs are explained. Rejuvenation methods are introduced, and their advantages and disadvantages are briefly mentioned. Then, the parameters affecting the degree of rejuvenation by elastostatic loading (EL) as a non-destructive method, and their effects on the microstructure, mechanical, and thermal properties of BMGs are summarized. In addition, the degree of rejuvenation obtained by EL is compared with those of other rejuvenation methods. Afterward, the reported works on the origin of EL rejuvenation (relaxation kinetics after EL rejuvenation) are critically discussed. It is clarified that in rejuvenated BMGs under EL, the residual strain after unloading is the sum of viscoelastic and unrecovered-anelastic strains, and the contribution of each depends on loading time and other treatment parameters. Therefore, a permanent deformation can be induced by EL. Finally, topics that deserve further study are proposed.